Digestion of Major Food (Leaf) Components by the Teak Defoliating Lepidopterous Larvae Hyblaea puera Cram (Hyblaeidae) and Eutectona machaeralis Walk (Pyralidae) - Mishra, S. C. (Indian Forester, 1992)
The digestion coeficient (D.C.%) of the fourth instar larvae of Hyblaea puera and Eutectona machaeralis varied from. 9. - 42.6% and 28.2 35.5% respectively, depending upon the host species. The proximate chemical composition of food and faecal matter of the larvae revealed that H. puera larvae (per gm food ingested) assimilate 71.0- 138.5 mg simple sugars;38.3-79.3 mg starch. some hexosans, tannins, etc.; 25.1-125.9 mg hemicellulose group; 2.0- 32.3 mg cellulose; 2.8 -162.4 mg lignin and 8.0-129.3 mg alcohol: benzene soluble components with different host species. In E. machaeralis larvae, the above figures ranged from 77.3-78.3 mg; 58.3 -101.5 mg; 24.0- 27.2 mg; 1.2 -1.9 mg; 1.2 -4.0 mg and 119.5-143.4 mg. The Tectona grandis is tbe most preferred host for both the larval species. The probable mechanism involved in degradation of polysaccaharides and lignin has also been discussed.